-6d+15=3(y-1)

Simple and best practice solution for -6d+15=3(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6d+15=3(y-1) equation:


Simplifying
-6d + 15 = 3(y + -1)

Reorder the terms:
15 + -6d = 3(y + -1)

Reorder the terms:
15 + -6d = 3(-1 + y)
15 + -6d = (-1 * 3 + y * 3)
15 + -6d = (-3 + 3y)

Solving
15 + -6d = -3 + 3y

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -6d = -3 + -15 + 3y

Combine like terms: 15 + -15 = 0
0 + -6d = -3 + -15 + 3y
-6d = -3 + -15 + 3y

Combine like terms: -3 + -15 = -18
-6d = -18 + 3y

Divide each side by '-6'.
d = 3 + -0.5y

Simplifying
d = 3 + -0.5y

See similar equations:

| -7(2n+3)=-7 | | x-0.22x=500.76 | | 72(3/4) | | n/8=2/3.2 | | 3y+5x=11 | | 3m-5+8m=17 | | 56+a+a^2=0 | | 56+a+a^2=0 | | 9/20=7.2/h | | 9/20=7.2/h | | 10(s-3)=-83 | | x-0.2x=498.20 | | x^6-6x^5+9x^4=0 | | (c-1)(-8c^2+c-5)= | | b/17.6=1/8.8 | | 5(n+3)=5 | | 7/9-7=-5 | | T=6-t | | 5d^2+20d+20=0 | | -1/8(4/5x-24)= | | 20.50x+395=1112.50 | | -1+5g=7g-9 | | fx=6x^5+3x^3+12x | | 24==v/3 | | -5n=-7-6n | | t/8.8=18/16 | | 9(n-12)=81 | | x^9-5x^8-24x^7=0 | | -4x-3(2x-16)=-32 | | 4(3n+1)=52 | | 6b=4b+10 | | 1/4(8x-4)= |

Equations solver categories